P15.02.B Spatial habitat analysis in high-grade gliomas combining perfusion, diffusion, and hypoxia features derived from multiparametric MRI and 18F-FAZA PET. (5th September 2022) - Bailo, M; Pecco, N; Callea, M; Scifo, P; Gagliardi, F; Fallanca, F; Picchio, M; Mortini, P; Falini, A; Castellano, A
Abstract: Background: Heterogeneity represents one of the main issues in high-grade gliomas (HGGs) management and presumably is the key to understanding treatment failure. Spatial habitat imaging embodies a novel, non-invasive method to cluster different tumor biological microenvironments and characterize intratumoral heterogeneity through a quantitative radiomic approach. So far, habitat imaging has been chiefly explored on morphological magnetic resonance imaging (MRI): the aim of our study was to evaluate this technique on advanced imaging techniques as perfusion (PWI) and diffusion (dMRI) MRI, as well as 18F-FAZA PET, to subdivide the tumor into different biological compartments. Materials and Methods: A preoperative PWI, dMRI, and 18F-FAZA PET acquisition was obtained in 17 HGG patients to assess intratumoral vascularization, cellularity, and hypoxia, respectively. A tumor mask was created including contrast-enhancing/necrotic regions on T1 imaging and surrounding FLAIR hyperintensity, and each parametric map (plasma volume from dynamic contrast-enhanced PWI, mean diffusivity from diffusion tensor imaging, and standardized uptake value from 18F-FAZA PET) underwent OTSU's binary clustering by grouping together voxels with high and low-intensity values. Cluster intersections were then generated by combining all possible high and low-intensity regions of each map, and the final habitat map was composed. Habitats' quantitative features, spatial distribution, and histopathological characteristics were analyzed. Results: The eight habitats generated were carefully inspected, and their distribution pattern, in relation to morphological landmarks (as contrast-enhancing, necrotic, infiltrative and edematous areas), showed an excellent reproducibility among different HGGs, offering complementary data to conventional imaging. A consistent correlation was noted between each habitat's awaited microenvironment and the corresponding histopathological characteristics among the ten patients for whom precise coordinates of stereotactic biopsies were available. Clusters considered more aggressive were more represented in WHO grade IV (vs. grade III) tumors. The habitat possibly representing edematous areas was significantly larger in IDH-1 wild-type (vs. IDH-1 mutated) tumors. Conclusions : PET and MRI hypoxia, perfusion, and tissue diffusion habitat maps proved an excellent reproducibility among HGGs and correlation with expected histopathological features, making it a way to characterize intratumoral heterogeneity. However, further study is needed to elucidate clinical implications and confirm the spatio-temporal evolution of the identified habitats. Funding: Italian Ministry of Health, grant number GR-2018-12365670; Italian Association for Cancer Research (grant IG 2014 Id.1524).